Spatial variation and structural change of the Barents Sea fish community - Fossheim, Maria; Johannesen, Edda; Primicerio, Raul; Aschan, Michaela (ICES, 2009)
We document the spatial patterns found in the Barents Sea fish community in relation to environmental parameters, analysing data from the ecosystem surveys covering the Norwegian part of the Barents Sea during 2004-2008 and comparing with earlier investigations of the deeper areas from the period 1992-2004. Changes in the ecosystem, expected on the basis of changing climate and harvest regimes may often go undetected due to strong focus on oceanography and commercial species of monitoring programs. Fish species that are not targeted by fishery are included in the analyses, providing valuable, additional ecological information on structural alterations. We identified species assemblages associated with different water masses and range of productivity of sea areas. Major changes in the structure of the fish community occur in this previously thought healthy, resilient and well-managed large marine ecosystem. The spatio-temporal analyses of the Barents Sea survey data from this decade shows that a new fish community structure is in place compared to the general community structure of the previous decades. An ecological regime shift in the 90-]ies might be speculated. The change is concurrent with a climatic regime shift and may be persistent.